The Effect of Cyber Security Training on Job Security in Mediated with Automotive Employees Work Compliance At PT. EX - Wilda Nur Fatimah; Mohammad Darul Fadli, Uus; Rosmawati, Ery (Research in Management of Technology and Business, 2025)
Rapid technological advancements in the automotive sector during the digitalization era have introduced digital security challenges, making cybersecurity training essential for individual and organizational protection. Job security and compliance enhance sustainability and operational efficiency. This research aims to explain the extent to which cybersecurity training impacts job security, with work compliance as a mediating variable. This study employs a quantitative descriptive methodology implemented at PT EX. The research involved 100 participants out of a total of 173 workers. Data collection included the distribution of questionnaires and analysis through the PLS-SEM approach, facilitated by SmartPLS 4.0 software. The findings indicate that cybersecurity training has a positive and significant impact on job security by 87.1%, with work compliance mediating 60.9% of the relationship between cybersecurity training and associated variables, while the remainder is affected by external factors not included in the research model.